The very 5′ end and the constant region of Ig genes are spared from somatic mutation because AID does not access these regions - Longerich, Simonne (The Rockefeller University Press, 2005)
Somatic hypermutation (SHM) is restricted to VDJ regions and their adjacent flanks in immunoglobulin (Ig) genes, whereas constant regions are spared. Mutations occur after about 100 nucleotides downstream of the promoter and extend to 1–2 kb. We have asked why the very 5′ and most of the 3′ region of Ig genes are unmutated. Does the activation-induced cytosine deaminase (AID) that initiates SHM not gain access to these regions, or does AID gain access, but the resulting uracils are repaired error-free because error-prone repair does not gain access? The distribution of mutations was compared between uracil DNA glycosylase (Ung)-deficient and wild-type mice in endogenous Ig genes and in an Ig transgene. If AID gains access to the 5′ and 3′ regions that are unmutated in wild-type mice, one would expect an “AID footprint,” namely transition mutations from C and G in Ung-deficient mice in the regions normally devoid of SHM. We find that the distribution of total mutations and transitions from C and G is indistinguishable in wild-type and Ung-deficient mice. Thus, AID does not gain access to the 5′ and constant regions of Ig genes. The implications for the role of transcription and Ung in SHM are discussed.